Pengaruh Green Investment dan Profitabilitas terhadap Nilai Perusahaan (Studi Kasus pada Perusahaan Pertambangan) - Setiawati, Setiawati; Yulia, Iis Anisa; Pranamulia, Agus (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
The purpose of this study is to analyze the impact of Green Investment and Profitability on firm value in mining companies listed on the Indonesia Stock Exchange in 2023. This research employs a quantitative research method. The data collection technique used is documentation by downloading financial statements and PROPER rating reports. The data analysis techniques applied include Descriptive Analysis, Classical Assumption Tests, Multiple Linear Regression Analysis, Coefficient of Determination, and Hypothesis Testing. The findings of this study indicate that the PROPER rating partially affects stock returns, Return on Assets (ROA) partially affects stock returns, and both the PROPER rating and ROA simultaneously affect stock returns.